AN ENERGY BALANCED AND NODES AWARE ROUTING PROTOCOL FOR ENERGY HARVESTING WIRELESS SENSOR NETWORKS - MANSURA, ANIKA (2020)
A set of randomly deployed sensor nodes that senses the data forms a wireless sensor network (WSN). Previously, the lifetime of WSNs was a big constraint since the nodes use non-rechargeable batteries with limited capacity. A promising solution to the energy issue is energy harvesting (EH). Routing protocol (RP) specifies a suitable path for data transmission from the source to the sink. Low energy adaptive clustering hierarchy (LEACH) is a popular hierarchical RP. In the literature, most of the available RPs based on LEACH for EH-WSNs have considered the traditional cluster head (CH) selection based on taking turns. Moreover, most of them have not considered the remaining energy and harvested energy in the CH selection process.